Causes and factors of deindustrialization in old industrial regions - O. V. Myasnyankina; A. A. Zaitsev (Вестник университета, 2023)
The subject of the study is the process of deindustrialization in the regions of the Central Federal District of Russia (hereinafter – CFD) and a set of causes and factors that determine industrial production reduction dynamics. The purpose of the study is to determine algorithms of industrial production recovery depending on the identified factors and causes of deindustrialization. Statistical groupings, analysis and synthesis method, comparative analysis of deindustrialization processes in the CFD regions were used as a methodology. Exclusive ways to restore industrial production in the CFD regions have been identified: innovation transfer based on the experience of techno-zones, special economic zones, territories of advanced development, and technoparks; integrated use of natural resources; modernization of high-tech industries; industrial agglomerations development in the peripheral territories of the federal subjects. The results of the study can be applied in the process of building strategic plans for revival of industrial production, first of all, when ensuring import substitution and strengthening the country’s defense capability. The process of deindustrialization is influenced by a group of factors that should be considered when establishing original sequence of strategic measures to revive industrial production.